Effect of maternal dexamethasone administration on daily fetal movement count and its correlation with Doppler studies and cardiotocography - Ali, Mohamed A.; Bayoumy, Hassan A.; Elshabrawy, Ahmed S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Decreased fetal movements is a frequent reason for unplanned consultations through the third trimester ranging between 4% and 16% in various populations it is often a sign of fetal compromise and associated with severe outcomes such as fetal growth restriction, preterm birth and fetal death therefore it is important to question the effect of maternal dexamethasone administration for fetal well-being and its relation on decreased fetal movement which is detected by Doppler studies and cardiotocography. Methods: The current study was performed on 220 pregnant women with gestational age between 28-34 weeks who received antenatal dexamethasone at Ain Shams university hospitals. Results: Regarding fetal movements, there was significant decrease in fetal movement at the 24th hour (Day 2) after 1st and 2nd doses of dexamethasone then re-increased at 48th hour and 72nd hour but still significantly lower than baseline. Conclusions: Administration of dexamethasone had no harmful effects on the fetuses or the mothers, except for a transient decrease of fetal movements in only after 24 hours of the first dose.